(untitled) (Innovative professional education, 2024)
Globalization of the economy and the war in Ukraine create new challenges for the formation and development of economic culture in the professional training of future technicians in transport technologies and management of road transport in the modern transport sector. The destruction of infrastructure, the blocking of ports, the rise in fuel prices, the shortage of personnel and the instability of the economic situation have a negative impact on the formation and development of economic culture in the professional training of future technicians in transport technologies and management of road transport in the modern transport sector. The war in Ukraine significantly complicated the problems of economic culture, the formation and development of economic culture in the professional training of future technicians in transport technologies and management of road transport in the modern transport sector. However, the war also gives Ukraine a chance to rebuild its logistics system and make it more resilient to challenges. This requires joint efforts of the state, the private sector and international partners.